2014
DOI: 10.1371/journal.pone.0101945
|View full text |Cite
|
Sign up to set email alerts
|

CACN-1/Cactin Plays a Role in Wnt Signaling in C. elegans

Abstract: Wnt signaling is tightly regulated during animal development and controls cell proliferation and differentiation. In C. elegans, activation of Wnt signaling alters the activity of the TCF/LEF transcription factor, POP-1, through activation of the Wnt/β-catenin or Wnt/β-catenin asymmetry pathways. In this study, we have identified CACN-1 as a potential regulator of POP-1 in C. elegans larval development. CACN-1/Cactin is a well-conserved protein of unknown molecular function previously implicated in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…It has been reported that [31][32][33]28]. Human Cactin has been reported to interact with IκBL, which is one of negative regulators of the NFκB signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that [31][32][33]28]. Human Cactin has been reported to interact with IκBL, which is one of negative regulators of the NFκB signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Human cactin was later found to physically and functionally interact with IκB-like protein (IκBL) and to be part of a negative feedback loop that controls NFκB transcriptional response (Suzuki et al, 2016), suggesting a conserved function for cactins in immune response and development (Atzei et al, 2010a). To date, cactin orthologs have been studied also in Toxoplasma gondii, Litopenaeus vannamei, Arabidopsis thaliana, Caenorhabditis elegans, and Danio rerio (Atzei et al, 2010b;Baldwin et al, 2013;Cecchetelli et al, 2016;Doherty et al, 2014;LaBonty et al, 2014;Szatanek et al, 2012;Tannoury et al, 2010;Zhang et al, 2014). In these organisms, cactin loss-of-function is associated with compromised cell viability and proliferation, and with developmental defects, highlighting the essentiality of cactin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These genes have been associated with cell proliferation in ovarian cancer and mitosis of ovarian germ cells. Downregulation of CACNA1 in somatic gonad cells through RNA interference (RNA i ) leads to an increase in POP1 expression, which negatively regulates cell proliferation (LaBonty et al, ). Basic FGF ( bFGF ) plays diverse roles in cell proliferation and differentiation during embryo development.…”
Section: Discussionmentioning
confidence: 99%